Targeting the Breast Cancer Kinome. Issue 1 (31st May 2016) - Miller, Samantha M.; Goulet, Daniel R.; Johnson, Gary L.
Abstract : Protein kinases are highly tractable targets for the treatment of many cancers including breast cancer, due to their essential role in tumor cell proliferation and survival. Sequencing of the breast cancer genome and transcriptome has defined breast cancer as a heterogeneous disease that is classified into five molecular subtypes: luminal A, luminal B, HER2‐enriched, basal‐like, and claudin‐low. Each subtype displays a unique expression profile of protein kinases that can be targeted by small molecule kinase inhibitors or biologics. An understanding of genomic changes, including mutations or copy number variations, for specific protein kinases and dependencies on kinases across breast cancer subtypes is allowing for a more rational design of targeted breast cancer therapies. While specific kinase inhibitors have had success in the clinic, including the CDK4/6 inhibitor palbociclib in combination with aromatase inhibitors in luminal breast cancer, patients often become resistant to treatment. An understanding of the mechanisms allowing cells to bypass targeted kinase inhibition has led to the development of combination therapies that are more durable in pre‐clinical studies. However, the heterogeneity of resistance mechanisms and rapid adaptability of the kinome through feedback regulation greatly inhibit the long‐term efficacy of combination kinase inhibitor therapies. It is becoming apparent that epigenetic inhibitors, such as HDAC and BET bromodomain inhibitors can block the transcriptional adaptability of tumor cells to kinase inhibitors and prevent the onset of resistance. Such novel combination therapies are currently showing promise in preclinical studies to markedly increase the durability of kinase inhibitors in breast cancer. J. Cell. Physiol. 232: 53–60, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Sequencing of the breast cancer genome and transcriptome has identified specific protein kinases as promising drug targets across the five molecular subtypes. While some kinase inhibitors have had success in the clinic, resistance to treatment often occurs. An understanding of the molecular mechanisms of resistance has allowed for the design of combination therapies which have the potential to block resistance in the clinic.